Utilisation of Labour among Pig Farmers in Northern Uganda - Mugonya, J.; Kalule, S.W.; Ndyomugyenyi, E.K. (African Crop Science Journal, 2020)
In many sub-Saharan countries, pig (Susscrofa domesticus) production is increasingly an important food security and income generating activity for smallholder farmers. This is attributed to the high prospects for vigilance of the pork market, driven by urbanisation, population growth and dietary transition towards more animal protein per capita. Therefore, increasing pig production is one of the viable pathways to get smallholder farmers out of poverty and food insecurity. Although there are extensive studies about the elements of pig production, such as feeding, breeding and space requirements; little work has been done on distribution of innovation behaviour and the socio-economic factors that influence labour utilisation in the region. The objective of this study was to determine the socio-economic factors that influence labour (family or hired) utilisation and distribution of innovation behaviour among pig farmers in Northern Uganda. Through a cross sectional survey and descriptive analysis, we characterised smallholder pig farmers in the northern Uganda by type of labour used for pig production, and explored the distribution of the dimensions of innovation behaviour (exploration, experimentation, adaptation and modification) among them. Results revealed that young educated farmers with non-farm employment, a smaller household size, belonging to a farmer group and who had many pigs were more likely to use hired labour than those with counter characteristics. There were significant differences in the number of farmers who exhibited the different dimensions of innovation behavior. Therefore, interventions to boost pig production through the use of hired labour should consider the socio-economic differences among farmers which determine labour constraints they face.
Keywords: Innovation behaviour, labour utilisation, pig production